Disability and social services: analysing accessibility in institutional complexity - Mira-Aladrén, Marta; Martín-Peña, Javier; Gil-Lacruz, Marta (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2023)
International laws, such as the Convention on the Rights of Persons with Disabilities, represent a step towards equity. They also imply both an increase in national and regional legislation, as well as greater institutional complexity, in order to make these rights effective. Therefore, we want to know how the right to universal accessibility has been implemented in legislation. A content analysis of 36 regulations related to disability and dependency in Aragon was carried out. Finally, it was detected that, despite certain advances, the adaptation of the regulations has not been consolidated, affecting the recognition of the rights of people with disabilities, especially the youngest and those with severe support needs.